2014
DOI: 10.1016/j.theriogenology.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Melphalan, alone or conjugated to an FSH-β peptide, kills murine testicular cells in vitro and transiently suppresses murine spermatogenesis in vivo

Abstract: New approaches to sterilizing male animals are needed to control captive and wild animal populations. We sought to develop a non-surgical method of permanent sterilization for male animals by administering the gonadotoxicant melphalan conjugated to peptides derived from the β-chain of follicle stimulating hormone (FSHβ). We hypothesized that conjugating melphalan to FSHβ peptides would magnify the gonadotoxic effects of melphalan while minimizing systemic toxicity. The ability of conjugates of melphalan and FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Finally, gonadotoxic effects of melphalan in males when administered during puberty have only been explored in preclinical studies where it was shown to impair the viability of germ cells. 141,150 Nevertheless, it was reported to be gonadotoxic at doses above 140 mg/m 2 . 13 Similarly, Thio-TEPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, gonadotoxic effects of melphalan in males when administered during puberty have only been explored in preclinical studies where it was shown to impair the viability of germ cells. 141,150 Nevertheless, it was reported to be gonadotoxic at doses above 140 mg/m 2 . 13 Similarly, Thio-TEPA.…”
Section: Discussionmentioning
confidence: 99%
“…No studies with patients treated during prepuberty/adolescence Germ cells: Reduction in viability. 150 Increase in oxidative stress; decrease in sperm numbers and motility. 141 Note:…”
Section: Clinical Findings Preclinical Findingsmentioning
confidence: 99%
“…Also, it requires parenteral administration, posing an acceptability obstacle, unless this mutant-adjudin conjugate can overcome the proteolysis of FSH polypeptide in the GI tract when the conjugate is orally administered, such as using the approach developed for oral delivery of insulin [86], including the use of nanoparticles containing absorption enhancers ( e.g., surfactants, zonula occludens toxins) and proteolytic enzyme inhibitors ( e.g., bacitracin, aprotinin, soybean trypsin inhibitor, polymer-inhibitor conjugates) [8688]. A recent study had also used this approach to conjugate a permanent male contraceptive melphalan (also a cytotoxic and gonado-toxic nitrogen mustard alkylating agent that kills murine testicular cells) to FSH-ß peptide to be used to target melphalan to the testis for chemical sterilization in wild-life animals and also pets such as cats and dogs [89]. …”
Section: Overcoming Tissue/cell Barriers For Drug Deliverymentioning
confidence: 99%
“…Specifically, our aim was to harness the mouse model to develop targeting vectors for two specialized cell populations; the Sertoli cells that nurse differentiating male germ cells and form the protective blood-testis-barrier [ 16 ], and the androgen producing Leydig cells, that reside within the interstitial space [ 17 , 18 ]. Our approach builds on previous evidence that peptides have utility for selectively delivering cytotoxic agents to the gonadotrophic cells of the pituitary [ 19 , 20 ] or the Sertoli cells of the testes [ 21 , 22 ], whereupon they transiently disrupt male fertility. To extend this response to achieve a state of permanent sterility, we elected to target cytotoxic agents to the Sertoli and Leydig cell populations concurrently, with the ultimate goal of ablating a sufficient number of these cells to permanently disrupt spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%